تقديرحجم الرحلات المتوقع تولدها من مناطق التوسع السكني الجديد لمدينة الحلة و اقتراح شبكة النقل العام لها / The Anticipated Volume of Flights from The New Residential Expansion Areas of Hilla City and Its Public Transport Network Proposal (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The volume of trips generated in the Hilla city and the expected trips generated in that area were studied. the effect of population expansion and urban development of the region on the movement of transport. Factors influencing transport movement, such as the use of land and social and economic situation for households in the study area, were evaluated. The calculation of trip generation was used by cross-sectional classification and category analysis for the purpose of predicting the expected tript size generated in the study area.The results showed that the study area suffers from a shortage of vehicles used in public transport.  The current capacity of vehicles is estimated to be approximately half of the demand for transport service. 40% of the population of the region suffers from a distance far away of public transport. After the completion of the development of the area (ie full occupancy of the residential complex), the demand for public transport will be doubled as the number of total trips using public transport increases from (21190) trips / day to 39446 trips / day. And that the public transport of the study area will need an increase in the number of vehicles used and also change the quality to cover both the current shortage and future increase.